Multi-professional IAPT CBT training: clinical competence and patient outcomes. Issue 6 (28th March 2019) - Liness, Sheena; Beale, Sarah; Lea, Susan; Byrne, Suzanne; Hirsch, Colette R.; Clark, David M.
Abstract: Background: There is international interest in the training of psychological therapists to deliver evidence-based treatment for common mental health problems. The UK Improving Access to Psychological Therapies (IAPT) programme, one of the largest training initiatives, relies on competent therapists to successfully deliver cognitive behaviour therapy (CBT) and promote good patient outcome. Aims: To evaluate an IAPT CBT training course by assessing if trainees' clinical skills improve during training and reach competency standards, and to report patient outcome for submitted training cases. To investigate a possible relationship between trainee competence and patient outcome. To explore professional differences during training. Method: CBT trainee ( n = 252) competence was assessed via audio recordings of therapy sessions at the beginning, middle and end of training. Patient pre- to post-treatment outcomes were extracted from submitted training cases ( n = 1927). Differences in professional background were examined across competence, academic final grade and tutorial support. Results: CBT trainees attained competence by the end of the course with 77% (anxiety recordings) and 72% (depression recordings) improving reliably. Training cases reported pre- to post-treatment effect sizes of 1.08–2.26 across disorders. CBT competence predicted a small variance in clinical outcome for depression cases. Differences in professional background emerged, with clinical psychologists demonstrating greater competence and higher academic grades. Trainees without a core professional background required more additional support to achieve competence. Conclusions: Part of a new CBT therapist workforce was successfully trained to deliver relatively brief treatment effectively. Trainees without a core profession can be successfully trained to competence, but may need additional support. This has implications for workforce training.